2007
DOI: 10.1111/j.1467-9701.2007.00887.x
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment, Economic Performance and Trade Liberalisation

Abstract: In a number of influential papers published by V. N. Balasubramanyam and collaborators during the decade of the 1990s, compelling arguments and supporting evidence was presented to indicate that export-promoting trade and investment strategies attract more and more productive inflows of foreign capital than do import-substituting strategies. This paper revisits these hypotheses in the context of more recent cross-section data and reports evidence to suggest that the earlier findings are robust. Copyright 2007 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…This variable has been significant in FDI inflows to many SSA countries with conscious policy to remove barriers to trade, which could only open up opportunities for FDI. Greenaway, Sapsford, & Pfaffenzeller (2007) assert that the more open the trade policy, the greater the economy's gravitational attraction to FDI. The recent scrutiny of the relationship between trade and investment is because the theory of trade and the theory of FDI have different origins, aims, and objectives.…”
Section: The Model Data and Variables Definitionsmentioning
confidence: 99%
“…This variable has been significant in FDI inflows to many SSA countries with conscious policy to remove barriers to trade, which could only open up opportunities for FDI. Greenaway, Sapsford, & Pfaffenzeller (2007) assert that the more open the trade policy, the greater the economy's gravitational attraction to FDI. The recent scrutiny of the relationship between trade and investment is because the theory of trade and the theory of FDI have different origins, aims, and objectives.…”
Section: The Model Data and Variables Definitionsmentioning
confidence: 99%
“…There are several reasons why foreign investors might prefer faster growing markets. For example, cost efficiency of production and the realization of economies of scale and scope in production are closely linked with market size (Blonigen et al 2007;Filippaios et al 2003;Greenaway et al 2007;Vernon 1966;Wang and Swain 1995). Other things equal, a growing market can be attractive to FDI because of the likelihood that a larger market will enable a more efficient scale of production (Agosin and Machado 2007;Carstensen and Toubal 2004).…”
Section: Economic Growth As An Fdi Attractormentioning
confidence: 99%
“…al 1996). Greenaway et al (2007) tested these hypotheses with data from 1990 to 2000 on a larger sample and confirmed that they still hold. Not only that, they also provided information that even within the sample of open economies, the ones with the highest levels of openness were more receptive to foreign capital.…”
Section: Introductionmentioning
confidence: 69%